COVID-19 in patients presenting with malaria-like symptoms at a primary healthcare facility in Accra, Ghana. - Issabella Asamoah; Mildred Adusei-Poku; Priscilla Vandyck-Sey; Allen Steele-Dadzie; Atta Senior Kuffour; Albert Turkson; Ivy Asantewaa Asante; Kantanka Addo-Osafo; Quaneeta Mohktar; Bright Adu; Yaw A Afrane; Kwamena W C Sagoe (PLoS ONE)
Background Malaria is a common and severe public health problem in Ghana and largely responsible for febrile symptoms presented at health facilities in the country. Other infectious diseases, including COVID-19, may mimic malaria due to their shared non-specific symptoms such as fever and headache thus leading to misdiagnosis. This study therefore investigated COVID-19 among patients presenting with malaria-like symptoms at Korle-Bu Polyclinic, Accra, Ghana. Methods This study enrolled 300 patients presenting with malaria-like symptoms aged ≥18yrs. After consent was obtained from study patients, two to three millilitres of whole blood, nasopharyngeal and oropharyngeal swab samples, were collected for screening of Plasmodium falciparum using malaria rapid diagnostic test, microscopy and nested PCR, and SARS-CoV-2 using SARS-CoV-2 antigen test and Real-time PCR, respectively. The plasma and whole blood were also used for COVID-19 antibody testing and full blood counts using hematological analyser. SARS-CoV-2 whole genome sequencing was performed using MinIon sequencing. Results The prevalence of malaria by microscopy, RDT and nested PCR were 2.3%, 2.3% and 2.7% respectively. The detection of SARS-CoV-2 by COVID-19 Rapid Antigen Test and Real-time PCR were 8.7% and 20% respectively. The Delta variant was reported in 23 of 25 SARS-CoV-2 positives with CT values below 30. Headache was the most common symptom presented by study participants (95%). Comorbidities reported were hypertension, asthma and diabetes. One hundred and thirteen (37.8%) of the study participants had prior exposure to SARS CoV-2 and (34/51) 66.7% of Astrazeneca vaccinated patients had no IgG antibody. Conclusion It may be difficult to use clinical characteristics to distinguish between patients with COVID-19 having malaria-like symptoms. Detection of IgM using RDTs may be useful in predicting CT values for SARS-CoV-2 real-time PCR and therefore transmission.